Cardiac Conduction Safety during Coadministration of Artemether-Lumefantrine and Lopinavir/Ritonavir in HIV-Infected Ugandan Adults. (20th March 2011) - Byakika-Kibwika, Pauline; Lamorde, Mohammed; Lwabi, Peter; Nyakoojo, Wilson B.; Okaba-Kayom, Violet; Mayanja-Kizza, Harriet; Boffito, Marta; Katabira, Elly; Back, David; Khoo, Saye; Merry, Concepta
Abstract : Background . We aimed to assess cardiac conduction safety of coadministration of the CYP3A4 inhibitor lopinavir/ritonavir (LPV/r) and the CYP3A4 substrate artemether-lumefantrine (AL) in HIV-positive Ugandans. Methods . Open-label safety study of HIV-positive adults administered single-dose AL (80/400 mg) alone or with LPV/r (400/100 mg). Cardiac function was monitored using continuous electrocardiograph (ECG). Results . Thirty-two patients were enrolled; 16 taking LPV/r -based ART and 16 ART naïve. All took single dose AL. No serious adverse events were observed. ECG parameters in milliseconds remained within normal limits. QTc measurements did not change significantly over 72 hours although were higher in LPV/r arm at 24 (424 versus 406;P = .02 ) and 72 hours (424 versus 408;P = .004 ) after AL intake. Conclusion . Coadministration of single dose of AL with LPV/r was safe; however, safety of six-dose AL regimen with LPV/r should be investigated.